SPECIAL semi‐LASER with lipid artifact compensation for 1H MRS at 7 T. Issue 3 (19th April 2012) - Fuchs, Alexander; Luttje, Mariska; Boesiger, Peter; Henning, Anke
Abstract The measurement of full metabolic profiles at ultrahigh fields including low concentrated or fast‐relaxing metabolites is usually achieved by applying short echo time sequences. One sequence beside stimulated echo acquisition mode that was proposed in this regard is spin echo full intensity‐acquired localized spectroscopy. Typical problems that are still persistent for spin echo full intensity‐acquired localized spectroscopy are B1 inhomogeneities especially for signal acquisition with surface coils and chemical shift displacement artifacts due to limited B1 amplitudes when using volume coils. In addition, strong lipid contaminations in the final spectrum can occur when only a limited number of outer volume suppression pulses is used. Therefore, an adiabatic short echo time (= 19 ms) spin echo full intensity‐acquired localized spectroscopy semilocalization by adiabatic selective refocusing sequence is presented that is less sensitive to strong B1 variations and that offers increased excitation and refocusing pulse bandwidths than regular spin echo full intensity acquired localized spectroscopy. Furthermore, the existence of the systematic lipid artifact is identified and linked to unfavorable effects due to the preinversion localization pulse. A method to control this artifact is presented and validated in both phantom and in vivo measurements. The viability of the proposed sequence was further assessed for in vivo measurements by scanning 17 volunteers using a surface coil and moreover acquiring additional volume coil measurements. The results show well‐suppressed lipid artifacts, good signal‐to‐noise ratio, and reproducible fitting results in accordance with other published studies. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.